Climate mitigation efficacy of anaerobic digestion in a decarbonising economy. (1st March 2022) - Styles, David; Yesufu, Jalil; Bowman, Martin; Prysor Williams, A.; Duffy, Colm; Luyckx, Karen
Abstract: Anaerobic digestion (AD) is at the interface of biowaste management, energy generation, food production and land-based carbon dioxide removal. Strategic deployment of AD requires careful scoping of interactions with prospective alternative biowaste management, energy generation technologies and land uses to ensure effective delivery of climate neutrality and circularity. There remains a need to assess the greenhouse gas (GHG) mitigation efficacy of AD in the context of future alternative (counterfactual) processes associated with differential rates of decarbonisation across energy, waste management and land (including agriculture) sectors. To address this gap, prospective life cycle assessment (LCA) is applied to AD deployment scenarios across three decarbonisation contexts, using the UK as an example. Food waste prevention and diversion to animal feed always achieve more GHG mitigation than AD, even with sustainable intensification of food and feed production. Compared with maize- or grass-biomethane transport fuel, solar electricity generation can avoid 16 times more fossil energy and afforestation can mitigate six times more GHG per hectare of land occupied. Transport biomethane is currently the most effective biogas use for GHG mitigation, but large-scale combustion of biogas for electricity or industrial heat generation is the most effective long-term option as transport is electrified and bioenergy carbon capture & storage (BECCS) is deployed. Prioritising waste prevention and diversion to animal feed (including via insect meal) instead of maximising AD deployment could simultaneously: offset an additional 10–15% of national GHG emissions; meet an additional 2–4% of national energy demand; free enough arable land to provide 20–21% of national recommended protein and kcal intake. However, AD is likely to remain the best option to manage substantial volumes of residual food wastes and manures that will remain available even if ambitious projections on waste prevention and diet change are realised. Graphical abstract: Image 1 Highlights: Consequential LCA of anaerobic digestion (AD) in future decarbonisation contexts GHG mitigation efficacy of AD declines as energy & transport systems decarbonise AD-crop cultivation is a highly inefficient land use for energy generation and GHG mitigation Carbon capture & storage could maintain effective mitigation from large-scale biogas use Sustainable niche for waste-AD alongside waste prevention & diversion to animal feed